The debate method in the development of critical thinking in Secondary Level students - Maiz Allpas, Yulino (2022)
The line of research of this work is: educational epistemology, and as a sub line of research: learning theories. Due to this disease caused by Covid-19, all the countries of the world and the Peruvian state were forced to quarantine their entire population to avoid contagion, and therefore the educational sector changed, from being a face-to-face education to a virtual one. Therefore, this research was developed in the middle of this context and had as a general problem the application of the debate method in the development of critical thinking in students of the 5th grade of secondary level of the Manuel Scorza Educational Institution of the district of Chuquis, Huánuco, 2021. Its objective was to determine if this method positively influences the development of this thought. The research was quantitative, applied type, experimental level and quasi-experimental design. The sample consisted of 28 students and its sampling was non-probabilistic, in which a written test was applied as a data collection instrument, both for Pre and Post Test. The results indicate that the debate method significantly influences the development of critical thinking in high school students, since it gives us a significance level of 0.000, in such a way that we can corroborate the 2 veracity of the general hypothesis. In conclusion, the results for the specific hypotheses show that the debate method also significantly influences the development of the dimension of analyzing information, inferring implications, proposing alternative solutions and arguing position.